The Necessity of Big Beautiful Mistakes (EAAE Annual Conference Proceedings, 2023)
There is a well-known need for innovative ways of tackling the burning challenges of today. Complex problem solving, critical thinking and creativity are key competences for the future according to World Economic Forum, 2020. It is therefore problematic that we all – not least architecture students – are embedded in friction-free systems and technologies that cloud the complexities of urgent issues.